Executive function mediates the prospective association between neurostructural differences within the central executive network and anti‐social behavior after childhood traumatic brain injury. (24th February 2021) - Ryan, Nicholas P.; Catroppa, Cathy; Hughes, Nathan; Painter, Felicity L.; Hearps, Stephen; Beauchamp, Miriam H.; Anderson, Vicki A.
Abstract : Background: Despite increasing evidence of a link between early life brain injury and anti‐social behavior, very few studies have assessed factors that explain this association in children with traumatic brain injury (TBI). One hypothesis suggests that childhood TBI elevates risk for anti‐social behavior via disruption to anatomically distributed neural networks implicated in executive functioning (EF). In this longitudinal prospective study, we employed high‐resolution structural neuroimaging to (a) evaluate the impact of childhood TBI on regional morphometry of the central executive network (CEN) and (b) evaluate the prediction that lower EF mediates the prospective relationship between structural differences within the CEN and postinjury anti‐social behaviors. Methods: This study involved 155 children, including 112 consecutively recruited, hospital‐confirmed cases of mild‐severe TBI and 43 typically developing control (TDC) children. T1‐weighted brain magnetic resonance imaging (MRI) sequences were acquired sub‐acutely in a subset of 137 children [TBI: n  = 103; TDC: n  = 34]. All participants were evaluated using direct assessment of EF 6 months postinjury, and parents provided ratings of anti‐social behavior 12 months postinjury. Results: Severe TBI was associated with postinjury volumetric differences within the CEN and its putative hub regions. When compared with TD controls, the TBI group had significantly worse EF, which was associated with more frequent anti‐social behaviors and abnormal CEN morphometry. Mediation analysis indicated that reduced EF mediated the prospective association between postinjury volumetric differences within the CEN and more frequent anti‐social behavior. Conclusions: Our longitudinal prospective findings suggest that detection of neurostructural abnormalities within the CEN may aid in the early identification of children at elevated risk for postinjury executive dysfunction, which may in turn contribute to chronic anti‐social behaviors after early life brain injury. Findings underscore the potential value of early surveillance and preventive measures for children presenting with neurostructural and/or neurocognitive risk factors.